An in situ study of microstructural strain localization and damage evolution in an (α+β) Ti-Al-V-Fe-Si-O alloy. (1st January 2023) - Kang, Jiyun; Oh, Hyun Seok; Wei, Shaolou; Zhu, Gaoming; Nakahata, Ikuho; Tasan, Cemal Cem
Abstract: Multi-phase titanium (Ti) alloys exhibit highly heterogeneous plastic deformation patterns. Understanding the micro-mechanisms of plastic deformation causing strain heterogeneity is thus of fundamental importance for enhanced manufacturability and in-service performance of Ti alloys. In this study, the critical microstructural factors responsible for microscopic strain localization are systematically investigated in an (α+β) Ti-Al-V-Fe-Si-O alloy by integrating the microstructural insights obtained from in situ microstructure-based digital image correlation (μ-DIC), in situ synchrotron X-ray diffraction (SXRD), and statistical analyses of strain localization incidents. The uniaxial tensile tests along the transverse direction reveal strain localization (i) across favorably oriented adjacent α grains (multi-grain strain localization) and (ii) along grain/phase boundaries (boundary strain localization), both of which suggest the strong influence of local crystallographic orientation on strain heterogeneity. The boundaries shared by soft and hard α grains are observed to be highly susceptible to strain localization, although ductile damage mechanisms are mostly delayed until the later stages of necking. While the majority of the (α+β) microstructure can co-deform to high strain levels without significant ductile damage evolution, micro-void nucleation and growth eventually initiate at the α/β phase interfaces, with work-hardening of the β phase. The insights provided through these in situ experiments highlight the importance of local texture in the strain localization and damage in (α+β) Ti alloys. Graphical abstract: Image, graphical abstract